2021
DOI: 10.3847/1538-3881/abdbb2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Spitzer Secondary Eclipses

Abstract: It is well-established that the magnitude of the incident stellar flux is the single most important factor in determining the day-night temperature gradients and atmospheric chemistries of short-period gas giant planets. However it is likely that other factors, such as planet-to-planet variations in atmospheric metallicity, C/O ratio, and cloud properties, also contribute to the observed diversity of infrared spectra for this population of planets. In this study we present new 3.6 and 4.5 micron secondary ecli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…The flux rise is noticeable on the right panel of Figure 2 in Wallack et al (2021), and was also noted by Goyal et al (2021). The latter authors did not elaborate, but Wallack et al (2021) discussed the decreasing efficiency of heat transport for temperatures exceeding ∼1500 K, albeit they did not emphasize the abruptness of the transition in their paper. We believe that this is the same phenomenon that we measure in this paper, in spite of the modest difference in the location of the transition.…”
Section: Noticed Previouslymentioning
confidence: 85%
“…The flux rise is noticeable on the right panel of Figure 2 in Wallack et al (2021), and was also noted by Goyal et al (2021). The latter authors did not elaborate, but Wallack et al (2021) discussed the decreasing efficiency of heat transport for temperatures exceeding ∼1500 K, albeit they did not emphasize the abruptness of the transition in their paper. We believe that this is the same phenomenon that we measure in this paper, in spite of the modest difference in the location of the transition.…”
Section: Noticed Previouslymentioning
confidence: 85%
“…Several studies have looked into trends in the ratio of 4.5-3.6 μm brightness temperatures (Kammer et al 2015;Wallack et al 2019;Garhart et al 2020;Wallack et al 2021). From our joint light-curve fits we measured brightness temperature ratios of 1.05 ± 0.14 (BLISS) and 1.13 ± 0.12 (PLD).…”
Section: Discussionmentioning
confidence: 96%
“…With the number of Jupiters with measured emission increasing, many studies have taken a statistical approach to exoplanet atmospheres, in both transmission (e.g., Baxter et al 2021) and emission (e.g., Garhart et al 2020;Wallack et al 2021). Here we compare WASP-34b against the literature of comparative exoplanetology to study how it fits into observed trends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 shows the heat redistribution (ε) of KELT-9b plotted along with other hot-Jupiters. In previous papers (Wallack et al 2021;Komacek & Showman 2016), it has been shown that for hot Jupiters, the incident stellar flux is the primary decider of the level of ε. However in Bell & Cowan (2018), they predict a rising heat redistribution for UHJ due to the H 2 dissociation and recombination increasing the heat transport around the planet.…”
Section: Albedo and Heat Redistributionmentioning
confidence: 99%